Emerging Coxsackievirus A6 Causing Hand, Foot and Mouth Disease, Vietnam - Nguyen To Anh; Le Nguyen Truc Nhu; Hoang Minh Tu Van; Nguyen Thi Thu Hong; Tran Tan Thanh; Vu Thi Ty Hang; Nguyen Thi Han Ny; Lam Anh Nguyet; Tran Thi Lan Phuong; Le Nguyen Thanh Nhan; Nguyễn Thanh Hùng; Truong Huu Khanh; et al. (2018)
Abstract Hand, foot and mouth disease (HFMD) is a major public health issue in Asia and has global pandemic potential. Coxsackievirus A6 (CV-A6) was detected in 514/2,230 (23%) of HFMD patients admitted to 3 major hospitals in southern Vietnam during 2011–2015. Of these patients, 93 (18%) had severe HFMD. Phylogenetic analysis of 98 genome sequences revealed they belonged to cluster A and had been circulating in Vietnam for 2 years before emergence. CV-A6 movement among localities within Vietnam occurred frequently, whereas viral movement across international borders appeared rare. Skyline plots identified fluctuations in the relative genetic diversity of CV-A6 corresponding to large CV-A6–associated HFMD outbreaks worldwide. These data show that CV-A6 is an emerging pathogen and emphasize the necessity of active surveillance and understanding the mechanisms that shape the pathogen evolution and emergence, which is essential for development and implementation of intervention strategies.